Significance of Brain Glucose Hypometabolism, Altered Insulin Signal Transduction, and Insulin Resistance in Several Neurological Diseases - Blázquez, Enrique; Hurtado-Carneiro, Verónica; LeBaut-Ayuso, Yannick; Velázquez, Esther; García-García, Luis; Gómez-Oliver, Francisca; Ruiz-Albusac, Juan Miguel; Ávila, Jesús; Pozo, Miguel Ángel (Frontiers in Endocrinology, 2022)
Several neurological diseases share pathological alterations, even though they differ in their etiology. Neuroinflammation, altered brain glucose metabolism, oxidative stress, mitochondrial dysfunction and amyloidosis are biological events found in those neurological disorders. Altered insulin-mediated signaling and brain glucose hypometabolism are characteristic signs observed in the brains of patients with certain neurological diseases, but also others such as type 2 diabetes mellitus and vascular diseases. Thus, significant reductions in insulin receptor autophosphorylation and Akt kinase activity, and increased GSK-3 activity and insulin resistance, have been reported in these neurological diseases as contributing to the decline in cognitive function. Supporting this relationship is the fact that nasal and hippocampal insulin administration has been found to improve cognitive function. Additionally, brain glucose hypometabolism precedes the unmistakable clinical manifestations of some of these diseases by years, which may become a useful early biomarker. Deficiencies in the major pathways of oxidative energy metabolism have been reported in patients with several these neurological diseases, which supports the hypothesis of their metabolic background. This review remarks on the significance of insulin and brain glucose metabolism alterations as keystone common pathogenic substrates for certain neurological diseases, highlighting new potential targets.